2022
DOI: 10.1007/s00221-022-06324-8
|View full text |Cite
|
Sign up to set email alerts
|

Peripersonal Space from a multisensory perspective: the distinct effect of the visual and tactile components of Visuo-Tactile stimuli

Abstract: Peripersonal Space (PPS) is defined as the space close to the body where all interactions between the individual and the environment take place. Behavioural experiments on PPS exploit multisensory integration, using Multisensory Visuo-Tactile stimuli (MVT), whose visual and tactile components target the same body part (i.e. the face, the hand, the foot). However, the effects of visual and tactile stimuli targeting different body parts on PPS representation are unknown, and the relationship with the RTs for Tac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 69 publications
1
2
0
Order By: Relevance
“…Without this simulation, the task is carried out by means of visual strategies, with errors in estimations that are not in uenced by distances and ramp inclination. These results provide evidence of the role of the current internal states of the body in space representation in the presence of chronic pain, thus supporting previous studies on healthy and deafferented groups (Beccherle et al, 2022;Scandola et al, 2020;Moro et al, 2023).…”
Section: Discussionsupporting
confidence: 90%
“…Without this simulation, the task is carried out by means of visual strategies, with errors in estimations that are not in uenced by distances and ramp inclination. These results provide evidence of the role of the current internal states of the body in space representation in the presence of chronic pain, thus supporting previous studies on healthy and deafferented groups (Beccherle et al, 2022;Scandola et al, 2020;Moro et al, 2023).…”
Section: Discussionsupporting
confidence: 90%
“…These findings contrast with the single-cell recording studies in monkeys showing that the receptive fields of the multisensory neurons are within RS 2 . However, one may hypothesise that the sensory facilitation reported in the behavioural studies and the neural mechanisms highlighted in the single-cell studies do not refer to the exact same multisensory integration process 90 . While the link between the two has been strongly advocated 30 , it is apparent that the behavioural multisensory facilitation effect in humans is more flexible than what was reported in single-cell studies.…”
Section: Discussionmentioning
confidence: 99%
“…As evidence, multisensory facilitation in behavioural studies has been found to be altered by the valence or meaning of the visual/auditory stimulus 69 , individual traits such as anxiety/phobia 46 , interoceptive traits 41 , bodily changes such as pregnancy 42 or limb immobilisation 91 , and even lockdown experience 88 . Moreover, a number of studies indicated that the visual/auditory stimulus does not have to target the same body part as the tactile stimulation to trigger multisensory facilitation 90 . This might be because the behavioural effects evidenced arose not only from the multisensory brain areas but also from their interaction with other brain areas such as those involved in body representation 92 and object-directed action control 7 .…”
Section: Discussionmentioning
confidence: 99%